The Cochrane Database of Systematic Reviews (Complete Reviews) 2000
DOI: 10.1002/14651858.cd003851
|View full text |Cite|
|
Sign up to set email alerts
|

Terazosin for benign prostatic hyperplasia

Abstract: The available evidence suggests that terazosin improves urinary symptoms and flow measures associated with BPO. Effectiveness is superior to placebo or finasteride, similar to other alpha-blockers but less than TUMT. Adverse effects were generally mild but more frequent than other alpha-blockers and associated with between a two-four fold increase in treatment discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…In men who have hypertension and cardiac risk factors, doxazosin monotherapy is associated with a higher incidence of congestive heart failure than are other antihypertensive agents. Terazosin's adverse effects, although generally mild, seem more frequent than other a-blockers' and are associated with a two-to fourfold increase in treatment discontinuation [10].…”
Section: Overflow Incontinencementioning
confidence: 98%
“…In men who have hypertension and cardiac risk factors, doxazosin monotherapy is associated with a higher incidence of congestive heart failure than are other antihypertensive agents. Terazosin's adverse effects, although generally mild, seem more frequent than other a-blockers' and are associated with a two-to fourfold increase in treatment discontinuation [10].…”
Section: Overflow Incontinencementioning
confidence: 98%
“…[19][20][21][22][23][24][25][26][27] (Level 1 Evidence, Grade A Recommendation). Alfuzosin, doxazosin, tamsulosin and terazosin are appropriate treatment options for LUTS secondary to BPH.…”
Section: Alpha-blockersmentioning
confidence: 99%
“…A systematic review of the available randomized controlled trials found that tamsulosin achieved an improvement in symptom scores that ranged from −20% to −48% and an increase in maximum flow rate (Q max ) that ranged from 1.2 to 4.0 ml/s (13-44% improvement) [Wilt et al 2002]. The main adverse effects related to tamsulosin use comprise asthenia, dizziness, rhinitis, symptomatic postural hypotension, ocular disorders [intraoperative floppy iris syndrome (IFIS)] and disorders of ejaculation [Oelke et al 2013].…”
Section: Introduction To Tamsulosin and Dutasteride Use For Bph-relatmentioning
confidence: 99%